Comparison of Bone Biomechanical Behavior around Three Different Mini-Implant Systems Employing Finite Element Method - Arabsolghar M; Mohammadi M; Razani M; Moosaali F (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Placement of mini-dental implants when single-tooth restorations are needed and the space is not sufficient to insert a standard diameter implant is indicated. There are many different mini-implant brands with various materials and surface characteristics; however, there are just few studies comparing them with each other. Objectives: In this study, finite element analysis (FEA) was applied to evaluate stress distribution in two different types of bone (D2, D3) around three different mini-implant systems (Dio, Dentis, and Osteocare). Materials and Methods: Three different mini- implant systems consisting of Dentis (Dentis Co., Ltd., Dalseo-gu, Daegu, Korea), Dio (DIO Medical Co., Jungwon-gu Seongnam-si, Kyunggi-do, S.Korea) and Osteocare (OsteoCare™, Slough, Berkshire, UK) were evaluated using FEA. At the same time, a vertical loading of 100N and a lateral loading of 30N at an angle of 45° were applied on the coronal part of the abutment in 2 different bone qualities: D2 bone quality, a thick layer (2 mm) of the compact bone surrounding a core of dense trabecular bone; and D3 bone quality, a thin layer (1 mm) of the cortical bone surrounding a core of dense trabecular bone of favorable strength. Stress levels in the bone surrounding mini-implants were analyzed using Ansys software (Ver.14), which provides the ability to simulate every structural aspect of a product. Descriptive statistics were used to compare the results. Results: After applying the loads and performing FEA, it was observed that in all three types of mini-implants for both static and dynamic analyses, the Von Mises stress values in D3 bone were more than those in D2 bone. The stresses in the cortical bone were obtained more than cancellous bone stresses. Conclusions: In all the studied systems, stress remained in the physiologic limits of the bone. In the cortical bone, stress distribution pattern in the three kinds of mini-implant was similar. Crestal bone stress, according to the amount of force applied, remained in acceptable levels.